Impact of Ecological Factors on Water quality goals - marif, arsalan (Agricultural Science, 2023)
A deeper knowledge of the processes that influence environmental elements in areas such as water management, consumer services, water reuse acceptability, and risk communication, among others. Also, as a result of the unique climate, soil features, and agricultural idiosyncrasies, water quality and water management for human welfare and the natural environment. Also, various kinds of contamination may also have an impact on aquatic habitats across the world. Trace metals are one of the most major pollutants that have harmed marine environments. Its release into the marine environment is caused by both natural and human activities. Erosion and pollution are two of the negative repercussions of agricultural operations on soil quality. Pollution from nutrient leaching and intrusion is one of the consequences for water resources. To choose the best long-term solutions for mitigating these effects, researchers should focus on developing an accurate water and soil quality monitoring system at many scales based on a functional evaluation. On the other hand, the review focuses on the influence of metals and nutrients on water quality for water usage and its impact on agricultural output. Its mean water quality great impact on natural and human on the other hand effect on environment and ecosystem. finally this review indicated that many  ecological factors positive effects on water quality goals.